Introduction: Comparative Performance Management and Accountability in the Age of Austerity. Issue 3 (2nd July 2016) - Grossi, Giuseppe; Hansen, Morten Balle; Johanson, Jan-Erik; Vakkuri, Jarmo; Moon, M. Jae
ABSTRACT: The five articles in this symposium examine the issues of comparative performance management and accountability in the age of austerity from different vantage points. Brusca and Montesinos carry out an international comparison of 17 countries studying key issues in the implementation of performance reporting by local governments. Using multicountry survey data, Wynen and Verhoest provide an understanding of the effect of organizational autonomy and external result control on the use of internal performance-based steering toward lower hierarchical levels in public sector organizations. Bjørnholt, Bækgaard and Houlberg study the link between fiscal austerity and politicians' use of performance information by using survey and documentary data from Danish municipalities. Grossi, Reichard, and Ruggiero examine the interest of politicians and public managers in the use of performance information for decision-making and monitoring the budget cycle provided in the newly established performance budgets of municipalities in Germany and Italy. Poocharoen and Wong examine performance management in different types of interagency collaborations, presenting six case studies of management projects in the field of natural resources. Taken together, these articles deepen our understanding of the fundamental and continuing shift toward use of performance measures in the public sector in the period of austerity, with both internal and external uses of performance information.